Improvement of recycled aggregate concrete using glass fiber and silica fume - Benemaran, Reza Sarkhani; Esmaeili-Falak, Mahzad; Kordlar, Morteza Sadighi (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2024)
Recycling concrete construction waste is a hopeful procedure toward environmentally friendly and sustainable construction. Recycled aggregate concretes (RACs) have been extensively studied in recent years, but few researches have been performed on concrete that is totally made with recycled aggregate (without natural aggregate). However, the low quality of recycled aggregate concrete, in comparison to conventional ones, has led researchers to investigate different approaches to improve its mechanical performance. To this aim, because of replacing 100% of fine and coarse aggregates with recycled coarse and fine aggregates, alkali-resistant glass fiber (AR-GF) (adding 1, 2, and 3%), and silica fume (SF) (replacing 5, 10, and 15% of dry cement weight) have been introduced as reinforcement and admixture to modify the defects’ mechanical behavior of RAC, respectively. In total, 384 concrete samples were made in 16 test groups of different ages of samples (7, 14, 28, and 56 days). To evaluate the morphologies of concrete with different mix designs after rupturing, scanning electron microscopy (SEM) analysis was carried out. The results depict that adding silica fume and glass fibers to the RAC leads to increases in compressive (CS) and splitting tensile strength (STS) in single and binary mixtures compared to conventional samples. However, adding fibers of more than 2% had a negative effect on CS and STS. In addition, to find the best solution for the mixtures, a technique for order preference by similarity to the ideal solution (TOPSIS) is employed, and the best mix design is determined with respect to their mechanical properties. From TOPSIS results, the M15G2 mix design could receive the highest value at 0.97803 compared to other mix designs. Overall, according to all three properties of compressive strength, tensile strength, consistency, and microstructural analysis, along with TOPSIS analysis, the sample containing 15% SF-2% AR-GF is introduced as the best combination.